Potential contribution of spinal interneurons to the etiopathogenesis of amyotrophic lateral sclerosis - Goffin, Luca; Lemoine, Damien; Clotman, Frédéric (Frontiers in Neuroscience, 2024)
Amyotrophic lateral sclerosis (ALS) consists of a group of adult-onset fatal and incurable neurodegenerative disorders characterized by the progressive death of motor neurons (MNs) throughout the central nervous system (CNS). At first, ALS was considered to be an MN disease, caused by cell-autonomous mechanisms acting specifically in MNs. Accordingly, data from ALS patients and ALS animal models revealed alterations in excitability in multiple neuronal populations, including MNs, which were associated with a variety of cellular perturbations such as protein aggregation, ribonucleic acid (RNA) metabolism defects, calcium dyshomeostasis, modified electrophysiological properties, and autophagy malfunctions. However, experimental evidence rapidly demonstrated the involvement of other types of cells, including glial cells, in the etiopathogenesis of ALS through non-cell autonomous mechanisms. Surprisingly, the contribution of pre-motor interneurons (INs), which regulate MN activity and could therefore critically modulate their excitability at the onset or during the progression of the disease, has to date been severely underestimated. In this article, we review in detail how spinal pre-motor INs are affected in ALS and their possible involvement in the etiopathogenesis of the disease.